rationalization of denominator
About us/Disclaimer  |  Contact Us

Rationalization of Denominator

Covid-19 has led the world to go through a phenomenal transition .

E-learning is the future today.

Stay Home , Stay Safe and keep learning!!!

In this section we will discuss rationalization of denominator.

Sometimes we come across expressions containing square roots in their denominators. In such an expression if the denominator is free from square roots then it will be easier to add/subtract/multiply or divide. To make the denominators free from square roots, we multiply the numerator and denominator by an irrational number. Such a number is called
rationalization factor.

Example : (1 - √3 ) / √2
As there is √2 in the denominator and we know that √2 x √2 = 2
So, multiply top and bottom by √2 .
[(1-√3) x √2] / (√2 x √2)
= [1√2 - √2 x √3] / 2 [ use distributive property]
=[ √2 - √6] /2

Note : Rationalization factor for :

1) 1/√a ------> √a
2) a + √b -------> a - √b
3) a - √b ---------> a + √b
4) √a + √b ----------> √a - √b
5) √a - √b ------------> √a + √b

Examples on rationalization of denominator

1) Rationalise the denominator of 2/√3
Solution :
We know that the rationalization factor for 1/√a is √a .
∴ 2/√3 = (2 x √3)/ (√3 x √3)
= 2√3/3
-----------------------------------------------------------------
2) Rationalise the denominator of 1/(3 - √2)
Solution :
We have,
1/(3 - √2) = 1(3 + √2) /(3 - √2)(3 + √2)
= (3 + √2)/( 9 – 2) [ use the identity of (a+b)(a-b) = a
2 - b 2 ]
= (3 + √2 )/ 7
-----------------------------------------------------------------
3) Solve : 3/(√3 + 1) + 5/(√3 – 1)
Solution :
3/(√3 + 1) + 5/(√3 – 1)
Rationalize the each term and then solve.
3/(√3 + 1) = 3 (√3 -1)/( √3 +1)( √3 -1)
=(3√3 – 3)/(3-1) = (3√3 – 3)/2 --------> (1)
5/(√3 – 1) = 5(√3 + 1)/( √3 -1)( √3 +1)
= (5√3 + 5)/(3-1) = (5√3 + 5)/2 --------> (2)
Add equation (1) and (2) we get,
(3√3 – 3)/ 2 + (5√3 + 5 )/2
= ( 3√3 – 3 + 5√3 + 5)/2
= (8√3 + 2)/2
= 2(4√3 + 1)/2
= 4√3 + 1
-----------------------------------------------------------------
4) √7(√35 - √7) = a + b√5 , find the value of a and b.
Solution :
√7(√35 - √7) = a + b√5
√7(√(7 x5) - √7) = a + b√5
√7(√7 x √5 - √7) = a + b√5
√7 x √7 x √5 - √7 x√7 = a + b√5 [ use a distributive law]
7√5 – 7 = a + b√5
-7 + 7√5 = a +b√5
∴ a = - 7 and b = 7.

Real-Numbers

Real Numbers
Representation of real-numbers on number line
Operations on Real Numbers
Rationalization of denominator

From real- number to number system

Home Page


Covid-19 has affected physical interactions between people.

Don't let it affect your learning.

privacy policy